Role of Avian Community in Reduction of Spodoptera Pest Population in Sugar Beet at Pune - Shivankar, S.B. Shivankar; Magar, S.B.; Shinde, V.D.; Ghodake, P.V.; Yadav, R.G. Yadav; Patil, A.S. (Our Nature, 2009)
Experiments were conducted at Vasantdada Sugar Institute, Pune in a RBD with three replications during 2005 to 2007 in sugar beet (var. posada) for control of Spodoptera litura Fab. The ornithological studies had shown the major avian community, Acridotheres tristis (Linnaeus), Passer domesticus (Linnaeus), Vanellus indicus (Boddaert), Corvus splendens (Vieillot), Centropus sinensis (Stephens), Pycnonotus cafer (Linnaeus), Eudynamys scolopacea (Linnaeus), with a relative abundance of 14.33, 13.26, 11.46, 5.73, 3.87, 3.54, and 2.79%, respectively. The reduction in mean S. litura population due to the pick up of the larvae by birds during three crop seasons ranged from 33.90 to 69.47%. Installation of minimum 15 bird perches/ha in 60 days after sugar beet sowing noticed effective considering the number of birds sittings (130.66/day), reduction in larval population of S. litura (39.99%), and root yield (71.36 ton/ha). Keywords: Sugar beet, Spodoptera, avian community, yield. doi: 10.3126/on.v6i1.1650 Our Nature (2008)6:19-25